2009
DOI: 10.1002/14651858.cd003240.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Day hospital versus outpatient care for people with schizophrenia

Abstract: of findings for the main comparison. DAY HOSPITAL versus OUTPATIENT CARE for people with schizophrenia near or on discharge DAY HOSPITAL versus OUTPATIENT CARE for people with schizophrenia near or on discharge Patient or population: patients with people with schizophrenia near or on discharge Settings: high income countries Intervention: DAY HOSPITAL versus OUTPATIENT CARE Illustrative comparative risks* (95% CI) Assumed risk Corresponding risk Outcomes Control DAY HOSPITAL versus OUTPATIENT CARE 242 (2 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 124 publications
0
11
0
4
Order By: Relevance
“…By applying the inclusion criteria on the full text of these reviews, we singled out 57 reviews for further critical appraisal. We only included the reviews that were of good methodological quality, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] which we assessed using the AMSTAR checklist 25 (17/57). As three of these 17 identified reviews did not include any studies, 9,13,15 we extracted data from 14 systematic reviews.…”
Section: Data Collectionmentioning
confidence: 99%
“…By applying the inclusion criteria on the full text of these reviews, we singled out 57 reviews for further critical appraisal. We only included the reviews that were of good methodological quality, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] which we assessed using the AMSTAR checklist 25 (17/57). As three of these 17 identified reviews did not include any studies, 9,13,15 we extracted data from 14 systematic reviews.…”
Section: Data Collectionmentioning
confidence: 99%
“…Outpatient/ambulatory clinics This has been described as "office-based practice which aims to provide support and maintenance therapy for people with mental disorders" [26]. Care may be delivered by a medical practitioner, psychiatrist, or specialized nurse, who may assess symptoms, identify adverse effects, adjust medication, assist with social problems, and deliver therapy.…”
Section: Long-term Community-based Residential Carementioning
confidence: 99%
“…It has been reported that psychosocial rehabilitation programs together with medication have increased treatment efficiency [2][3][4] and patients' quality of life 5,6 and have decreased family load 7 . Day hospital programs have been reported to have results that include: i) higher recovery in symptoms when compared to outpatients, ii) faster recovery and lower care costs, iii) lower relapse rates, and iv) decreases in the frequency and duration of hospitalizations 8 . Therefore, in mental diseases that lead to heavy disability like schizophrenia, a contemporary and up-to-date understanding includes a multidimensional approach to increasing functionality and decreasing the destructive results of the disease 3,9,10 .…”
Section: Introductionmentioning
confidence: 99%